RAPID ISOMERIZATION OF ALKYNOL BY POTASSIUM AMINOPROPYLAMIDE REAGENT - Hendig Winarno (Universitas Gadjah Mada, 2007)
Terminal alkynol (w-alkynol) is an intermediate compound in synthesis of a potent anticancer agent, namely C-16 alkynic fatty acid. For synthesis of this intermediate compound, it is needed to synthesize the appropriate internal alkynol, namely 2-nonyn-1-ol (10), 2-undecyn-1-ol (11), and 2-heptyn-1-ol (12), subsequently to convert these internal alkynol into terminal alkynol, namely 8-nonyn-1-ol (7), 10-undecyn-1-ol (8), and 6-heptyn-1-ol (9), an isomerization reaction was needed. Based on the method which developed by ABRAMS by using potassium 3-aminopropylamide (KAPA) reagent, the isomerization reaction could be done within 5 minutes in 93-94% yield.